Effects of Additional Exercise Volume on Weight Loss, Oxidative Stress, and Inflammation in Young Wrestling Athletes - Kheirandish, Reza; Rahmani, Ahmad; Gorzi, Ali; Shaabani Ezdini, Ebrahim; Sadeghi , Atefeh (International Journal of Sport Studies for Health, 2024)
Background: Maintaining an optimal weight is essential for wrestlers, given their competition in weight-classified categories. However, many wrestlers resort to unhealthy methods of rapid weight loss, such as drastic caloric restriction and dehydration, which can adversely affect their overall wellbeing.Objective: This study aimed to examine the impact of a two-week increase in exercise volume on weight loss, serum oxidative stress, and inflammation in young wrestlers.Methods and Materials: Twenty wrestlers (aged 15-19, weight 63.47 kg) participated in a 2-week exercise intervention in addition to their regular weekly wrestling drills. The intervention consisted of resistance training, high-intensity interval training, and speed training. Wrestlers weighed daily over 2-week span. The participants' superoxide dismutase (SOD), malondialdehyde (MDA), total antioxidant capacity (TAC), and serum interleukin-6 (IL-6) were measured both before and after the intervention. Data were analyzed using the paired t-test conducted through SPSS software, with a significant level set at p < 0.05.Results: The 2-week intervention resulted in significant weight loss (p